High-protein-pufa supplementation, red blood cell membranes, and plasma antioxidant activity in volleyball athletes - Malaguti, M.; Baldini, M.; Angeloni, C.; Biagi, P.; Hrelia, S. (International Journal of Sport Nutrition and Exercise Metabolism, 2008)
The authors evaluated the role of a high-protein, low-calorie, polyunsaturated fatty-acid (PUFA) -supplemented diet on anthropometric parameters, erythrocyte-membrane fatty-acid composition, and plasma antioxidant defenses of nonprofessional volleyball athletes. The athletes were divided in two groups: One (n = 5) followed the Mediterranean diet, and the other (n = 6) followed a high-protein, low-calorie diet with a 3-g/day fish-oil supplementation. All the athletes had anthropometric measurements taken, both at the beginning and at the end of the study, which lasted for 2 months. Body-mass index and total body fat were significantly diminished in the second group, while they remained unchanged in the first. Plasma total antioxidant activity (TAA) was significantly increased in the plasma of both groups, with no differences between the groups, suggesting that physical activity, not the different diets, is the main contributor to the increase of plasma TAA. The second group showed a significant increase in erythrocyte-membrane PUFA content and in the unsaturation index value (UI) because of the fish-oil supplementation.A high-protein, low-carbohydrate, fish-oil-supplemented diet seems to be useful only when the aim of the diet is to obtain weight loss in a short-term period. The significant increase in the UI of erythrocyte membranes indicates the potential for harm, because a high intake of PUFA might increase susceptibility to lipid peroxidation not counterbalanced by a higher increase in TAA. Adherence to the Mediterranean diet seems to be the better choice.